Sacred Bonds Beyond Beliefs: Interfaith and Traditional Marriage Rituals and Rites in Hinduism Religion - Murshida Khatun; Md Amirul Islam; Mst Baly Khatun; Mst. Yasmin Ara Ema; Sharmin Akter Sompa; Md. Ariful Islam; Md. Limon Mia; Md. Maruf Hossen; Masud Rana (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This study explores Hindu marriage history, system, ritual, rite, type, and interfaith marriage in Hinduism and various castes, and the Bollywood movie industry in India, focusing on the sacred bonds formed beyond religious beliefs. It tries to clarify how Hindu marriage rituals are components of various religions and traditional customs among castes, encouraging inclusivity and peace. This paper uses descriptive qualitative methodology through the analysis of past scholars’ papers, chanting mantras, and the last 120 years of the Indian census for the women and male ratio per thousand. Hinduism embraces diversity and adapts to accommodate various religious and cultural backgrounds, allowing couples to celebrate their love while honoring their respective traditions. Especially in Bollywood, where interfaith marriage is common. The last 10 decades have seen a decrease in the number of women, but according to the 2021 Indian Census, the women's ratio has increased over the last 12 decades. The situation will increase the number of interfaith couples, and interfaith marriage rituals in Hinduism will serve as a bridge between different faiths, promoting unity and understanding among diverse communities.